2015
DOI: 10.1002/ccd.26272
|View full text |Cite
|
Sign up to set email alerts
|

Increased bleeding risk during percutaneous coronary interventions by arterial hypertension

Abstract: Arterial hypertension is associated with increased risk of bleeding during PCI procedures. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Hypertensive patients also have more bleeding complications after percutaneous coronary intervention. 45 Even in hypertensives without AF or any antithrombotic therapy, for example, in survivors of intracranial hemorrhage of any cause, inadequate BP control was strongly associated with about 4-fold higher risk of the hemorrhage recurrence. 46 Important data on the role of hypertension in AF have been provided by recent clinical trials.…”
Section: Balancing Stroke and Bleeding Risk In Hypertension And Afmentioning
confidence: 99%
“…Hypertensive patients also have more bleeding complications after percutaneous coronary intervention. 45 Even in hypertensives without AF or any antithrombotic therapy, for example, in survivors of intracranial hemorrhage of any cause, inadequate BP control was strongly associated with about 4-fold higher risk of the hemorrhage recurrence. 46 Important data on the role of hypertension in AF have been provided by recent clinical trials.…”
Section: Balancing Stroke and Bleeding Risk In Hypertension And Afmentioning
confidence: 99%
“…In patients at high risk of ischemic events, DAPT could prevent fatal thrombotic events . However, prolonged DAPT is associated with increased bleeding and adverse outcomes; it is thus of vital importance to establish optimal DAPT duration . Indeed, bleeding concerns, in parallel with the improved biocompatibility of newer generation stents have led to more uncertainty after several recent randomized controlled trial(s) (RCT) did not show any benefit of prolonging DAPT to 1 year or more versus a shorter course.…”
Section: Introductionmentioning
confidence: 99%
“…A large retrospective analysis of the Intracoronary Stenting and Antithrombotic Registry randomized controlled trial populations found that patients with a history of hypertension had a 41% greater risk for bleeding events, in particular for non-access-site bleeding (p=0.002), whereas systolic blood pressure at the time of PCI increased the risk for access site bleeding (p=0.018). 10 Patients with hypertension had similar one-year mortality compared with normotensive patients; however, mortality was significantly higher in hypertensive patients with a bleeding event. Thus, optimizing blood pressure control prior to elective, supported PCI is important.…”
Section: Hypertensionmentioning
confidence: 91%